2011
DOI: 10.1159/000324463
|View full text |Cite
|
Sign up to set email alerts
|

Arg16Gly β2-Adrenergic Receptor Gene Polymorphism in Japanese Patients with Aspirin-Exacerbated Respiratory Disease

Abstract: Background: There has been no report that investigated β2-adrenergic receptor (ADRB2) gene polymorphism in patients with aspirin-exacerbated respiratory disease (AERD). Methods: DNA in the specimens in three groups of study subjects classified patients with AERD, patients with aspirin-tolerant asthma (ATA) and normal controls was extracted, and the target DNA sequence of the ADRB2 was amplified using a set of primers to generate an amplicon of 219 bp in length. Allelic discrimination assay for singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…In addition, one article [28] was excluded as it was in Polish. Ultimately, 46 articles [8]–[11], [13], [29]–[69] met the inclusion criteria (Figure 1). The characteristics of each article are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, one article [28] was excluded as it was in Polish. Ultimately, 46 articles [8]–[11], [13], [29]–[69] met the inclusion criteria (Figure 1). The characteristics of each article are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…52, 54, 151 A candidate gene approach has identified an association between CRS and variation in the gene for the adrenergic beta-2 receptor ( ADRB2 ), 152 which has been linked to AERD, asthma exacerbations, and bronchodilator response among patients with asthma. 153-155 A recent study of Chinese patients (306 CRSwNP, 332 CRSsNP, 315 controls) has identified an association between CRSwNP, CRSsNP, and Ring1 and YY1 binding protein ( RYBP ) (CRSwNP: OR, 2.76, P = 3.24 × 10 −6 ; CRSsNP: OR, 2.45, P = 4.12 × 10 −5 ); these findings remained significant after correction for multiple statistical testing. 91 RYBP is a pleomorphic molecule that binds transcription factors and apoptotic mediators 91 ; its direct effect on CRS pathogenesis remains unclear.…”
Section: Genetics Of Crs: Current State Of the Field And Limitations mentioning
confidence: 99%
“…The possible role of arachidonic acid metabolites, such as LTs, in the pathogenesis of AERD has also been suggested (1). We recently reported that the Arg16Gly β 2 -adrenergic receptor gene polymorphism in AERD is different from that in ATA (24). In the present study, we extended our investigations to explore the genetic determinations of AERD.…”
Section: Discussionmentioning
confidence: 58%
“…The target DNA sequence of CRTH2 -466T>C was amplified using a set of primers (forward 5'-GAGCTGCATGGAGGATCTGT-3'; reverse 5'-AGGACTCCTTTTTCCCATCC-3'). Allelic discrimination assay for SNPs relating to the expression of TBXA2R +795T>C and CRTH2 -466T>C (rs11085026 and rs634681, respectively) was carried out using the previously described SNP detection system, sequence-specific thermalelution chromatography (23,24). All subjects and researchers remained unaware of the genotype until the final analysis.…”
Section: Methodsmentioning
confidence: 99%